Connecting HRM and change management: the importance of proactivity and vitality. Issue 4 (13th July 2015) - Tummers, Lars; Kruyen, Peter M.; Vijverberg, Dominique M.; Voesenek, Tessa J.
Abstract : Purpose: – Organizations are continuously under pressure to adapt to changing circumstances. Job proactivity and vitality are important in changing environments. For instance, vital employees can better deal with change because they possess more energy. However, it is still unclear how organizations can stimulate proactivity and vitality. The purpose of this paper is to connect HRM and change management by analyzing how HRM practices can stimulate job proactivity and vitality. Design/methodology/approach: – The authors used survey data collected in three large public healthcare organizations in the Netherlands ( n =1, 507) to investigate the effects of five important HRM practices on proactivity and vitality. Analyses were performed using structural equation modeling. Findings: – Results suggest that three HRM practices are particularly effective for improving proactivity and vitality: high autonomy, high participation in decision making and high quality teamwork. Based on these results, the authors discuss the possibilities of using HRM to improve employees' abilities to deal with organizational change. Originality/value: – This study is one of the first to empirically connect HRM to change management. Furthermore, it uses new concepts derived from positive psychology (job proactivity and vitality) to show how HRM can be beneficial for organizational change.